New Vistas in Natural Resources Law - Shameem, Shaista; Arjjumend, Hasrat (TGI Books/ The Grassroots Institute, 2024)
The book "New Vistas in Natural Resources Law" is a pioneering exploration into the dynamic and multifaceted realm of environmental governance, cantered around crucial keywords such as Environmental Law, Natural Resources Management, Forest Laws, Biodiversity Laws, Indigenous Peoples, Conservation Policies, Rangeland Policies, Environmental Policy, Agrarian & Land Laws, and Mining Related Laws. Authored by experts at the intersection of law and environmental science, this comprehensive volume offers a panoramic view of the evolving legal landscape governing our planet's vital natural resources. The book commences with an in-depth analysis of Forest Laws, establishing the foundational principles that guide the intricate relationship between human activity and the environment. It scrutinizes international conventions, regional agreements, and domestic legal frameworks, illustrating how these instruments shape the sustainable management of natural resources on a global scale. A focal point of the narrative is Natural Resources Management, exploring the complexities of balancing resource utilization with the imperative of conservation. The book investigates innovative strategies for managing diverse ecosystems, ranging from forests to rangelands, and delves into the legal frameworks that underpin sustainable practices. Forest Laws and Biodiversity Laws are dissected in separate chapters, providing a detailed examination of legal instruments designed to protect and preserve these critical components of our natural heritage. The book assesses the effectiveness of legislation in addressing deforestation, biodiversity loss, and the protection of endangered species. The rights and contributions of Indigenous Peoples take centre stage as the book explores how legal frameworks intersect with traditional knowledge and land use practices. It critically examines the evolving legal landscape that recognizes and safeguards the rights of indigenous communities in the context of natural resources management. Conservation Policies and Rangeland Policies are explored as integral components of environmental governance, shedding light on the legal strategies employed to balance the needs of agriculture, conservation, and sustainable land use. Environmental Policy emerges as a cross-cutting theme, with the book examining the development, implementation, and impact of policies aimed at addressing pressing environmental challenges. It evaluates the role of legal frameworks in shaping policy decisions and fostering effective environmental management. Agrarian & Land Laws are scrutinized for their role in shaping land use practices and mitigating conflicts arising from competing interests. The book investigates how legal instruments can balance the needs of agriculture, urban development, and conservation. The legal dimensions of mining-related activities take centre stage, addressing the challenges and opportunities presented by extractive industries. The book explores the role of law in regulating mining practices, mitigating environmental impacts, and ensuring responsible resource extraction.
Keywords: Natural resources -- Law and legislation.